104k views
4 votes
Simplify;a/2(a+b)+b/2(a-b)​

User Selvagsz
by
7.5k points

2 Answers

1 vote


(a)/(2(a+b))+(b)/(2(a-b))=\\\\(a(a-b))/(2(a+b)(a-b))+(b(a+b))/(2(a+b)(a-b))=\\\\(a^2-ab)/(2(a^2-b^2))+(ab+b^2)/(2(a^2-b^2))=\\\\(a^2+b^2)/(2(a^2-b^2))

User Eusid
by
8.3k points
1 vote

Answer:


\huge\boxed{\sf (a^2+b^2)/(2(a^2-b^2))}

Explanation:

=>
\sf (a)/(2(a+b)) + (b)/(2(a-b))

LCM = 2(a+b)(a-b)

=>
\sf (a(a-b)+b(a+b))/(2(a+b)(a-b))

Simplifying further

=>
\sf (a^2-ab+ab+b^2)/(2(a^2-b^2))

=>
\sf (a^2+b^2)/(2(a^2-b^2))

User Havvg
by
7.2k points